Institutional Framework for Human Rights Protection in Africa: The African Commission on Human and Peoples’ Rights - Konjević, Tena (Regional Human Rights Protection Systems Outside Europe, 2026)
The African Commission on Human and Peoples’ Rights stands as a cornerstone of human rights protection in Africa. This chapter examines the Commission’s evolution, structure, and function within the broader context of human rights in Africa. We trace the historical roots of human rights abuses on the continent, highlighting the exploitation and deprivation endured during colonial times, and the establishment of the Organization of African Unity (OAU) in 1963 as a response to these injustices. We then analyse the adoption of the African Charter on Human and Peoples’ Rights (Banjul Charter) in 1981, a landmark document that solidified the commitment to protecting human rights in Africa. Furthermore, the chapter delves into the structure and composition of the African Commission, established in 1987 as a quasi-judicial body tasked with monitoring the implementation of the Charter. We examine the Commission’s unique position as a sui generis entity, operating between the Charter’s aspirations and the realities of Africa’s political landscape. We explore its key functions: reporting, communication, and promotional activities. The reporting procedure involves reviewing reports submitted by African states on their human rights records, while the communication procedure handles complaints alleging human rights violations. We also examine the Commission’s promotional activities, which aim to raise awareness of human rights and promote the implementation of the Charter. Finally, the chapter explores the Commission’s strengths and weaknesses, acknowledging its challenges in fulfilling its mandate. These challenges include limited resources, a lack of awareness of the Charter and its procedures, a lack of political will on the part of some African states, and insufficient enforcement mechanisms. The chapter concludes by discussing the Commission’s potential for advancing human rights in Africa, emphasizing the need for greater support from African states, international organizations, and civil society.Keywords: African Commission on Human and Peoples’ Rights, African Charter on Human and Peoples’ Rights, human rights, African Union